Pediatric Cullen gangrene: Case report of postoperative pyoderma gangrenosum in a preterm infant with a complex gastrointestinal malformation - Diez, Sonja; Syed, Julia; Müller, Hanna; Besendörfer, Manuel; Schellerer, Vera (International Journal of Surgery Case Reports, 2020)
Introduction: Pyoderma gangrenosum (PG) is a rare condition in infants, children and adolescents. The postoperative variant of this rapidly progressive ulceration is known as Cullen gangrene. Only a few case reports of pediatric Cullen gangrene have been published. Presentation of case: We present a male infant (gestational age 31 + 6 weeks) with gastroschisis and intrauterine volvulus. After multiple operations due to his complex gastrointestinal malformation, the patient showed classical symptoms of postoperative PG (PPG) 4 weeks after birth. Diagnosis could be made early in an interdisciplinary approach, differentiating intraabdominal infection (vancomycin resistant enterococcus (VRE), candida albicans) from epifascial occurrence. Treatment with high-dose steroids and immunoglobulins was initiated immediately and led to rapid recovery. Discussion: The unusual combination of a complex gastrointestinal malformation and an intraabdominal infection with VRE and candida albicans made the diagnosis difficult. However, early diagnosis is crucial in the treatment of Cullen gangrene. Conclusion: This is the first case report of Cullen gangrene presenting in an infant (at 4 weeks of age).
CRIS-Team Scopus Importer:2020-01-21
Keywords: Cullen gangrene; Gastroschisis; Pediatric surgery; Pyoderma gangrenosum